Nation and Religion: Perspectives on Europe and Asia by Peter van der Veer and Hartmut Lehmann, eds. (Princeton University Press, 1999. 222 pages.) (American Journal of Islam and Society, 2001)
This important new addition to the growing body of literature onnationalism, religion, and religious nationalism is the product of aconference on "Religion and Nationalism in Europe and Asia", held in1995 at the University of Amsterdam. Princeton University Press is in general hesitant when it comes to publishing edited volumes; it has donewell to make an exception for this one. While many edited collections,particularly those that grow out of conferences, are at best of inconsistentquality and at worst entirely lacking in coherence, van der Veer andLehmann's Nation and Religion is striking both for the high quality of eachindividual essay it contains and for the depth and force of the overallargument that emerges from the volume as a whole.That argument is an important and provocative one: that modernity,contrary both to modernity's own depiction of itself and to much historiographyof the modem period, is not characterized by the eradication ofreligion's relevance to politics. On the contrary, the varied chapters in thisbook show religion to be a near-ubiquitous feature of the politicallandscape and discourse of the so-called "First" and "Third" Worlds alike.The volume is made up of ten chapters that together deal with therelationship between religion and politics in the Netherlands, Great Britain,India, and Japan. The fullest coverage is given to India, which isapproached from different perspectives in four different chapters: van derVeer's "The Mod State: Religion, Nation, and Empire in Victorian Britainand British India", Susan Bayly's "Race in Britain and India", ParthaChatterjee's "On Religious and Linguistic Nationalisms: The SecondPartition of Bengal", and Barbara Metcalf's "Nationalism, Modernity, andMuslim Identity in India before 1947". This particular focus on India is areflection both of van der Veer's own specific interests and training and ofthe fact that India - both British imperial and modem national - lends itselfparticularly well to analysis concerned with the interplay between religion,politics, and modem nationalisms.The British dimension of van der Veer and Bayly's chapters is expandedby Hugh McLeod in his contribution on "Protestantism and BritishNational Identity, 1815-1945". The volume also includes two chapters onthe Netherlands (Peter van Rooden's "History, the Nation, and Religion:The Transformations of the Dutch Religious Past", and Frans Groot's"Papists and Beggars: National Festivals and Nation Building in theNetherlands during the Nineteenth Century") and one on Japan (HarryHarmtunian's "Memory, Mouming, and National Morality: YasukuniShrine and the Reunion of State and Religion in Postwar Japan").Despite the diversity of time and place reflected in the volume, the essaysread remarkably well together as a whole - the result of a clearly-conceivedand carefully edited project. Additional coherence comes from the ...